Assessment and prevention of cytomegalovirus infection in allogeneic hematopoietic stem cell transplant and in solid organ transplant: A multidisciplinary consensus conference by the Italian GITMO, SITO, and AMCLI societies. Issue 10 (6th August 2019) - Girmenia, Corrado; Lazzarotto, Tiziana; Bonifazi, Francesca; Patriarca, Francesca; Irrera, Giuseppe; Ciceri, Fabio; Aversa, Franco; Citterio, Franco; Cillo, Umberto; Cozzi, Emanuele; Gringeri, Enrico; Baldanti, Fausto; et al.
Abstract: Cytomegalovirus (CMV) remains a major cause of morbidity and mortality in allogeneic hematopoietic stem cell transplantation (allo‐HSCT) and solid organ transplantation (SOT) recipients. In view of the uncertainties on the assessment and prevention of CMV infection in both transplant procedures, three Italian scientific societies for HSCT and SOT and for Clinical Microbiology appointed a panel of experts to compose a framework of recommendations. Recommendations were derived from a comprehensive analysis of the scientific literature and from a multidisciplinary consensus conference process. The lack of adequate clinical trials focused on certain diagnostic procedures, and antiviral intervention forced the panel to use the methods of consensus for shaping some recommendations. Recommendations concerning the two types of transplant were given for the following issues: assessment of pretransplant CMV serostatus, immunological monitoring after transplant, CMV prophylaxis with antivirals, CMV preemptive strategy, and CMV prophylaxis with immunoglobulin infusion and with adoptive immunotherapy. The questions raised by and the recommendations resulting from this consensus conference project may contribute to the improvement of certain crucial aspects of the management of CMV infections in allo‐HSCT and in SOT populations.